LOCAL INSTRUCTIONAL THEORY OF DERIVATIVE TOPICS BASED ON REALISTIC MATHEMATICS EDUCATION FOR GRADE XI SENIOR HIGH SCHOOL STUDENTS - Armiati, Armiati; Sari, Ratih Permata (Program Studi Pendidikan Matematika FKIP Universitas Pattimura, 2022)
This study discusses the development of learning design for derivative topics based on Realistics Mathematics Education (RME). The design developed is different from the designs that have been developed by previous researchers, where in this study, the derivative concept was introduced through the flying fox trajectory, which refers to students' understanding of limits and average velocity. This development aims to obtain a valid, practical, and effective learning design in derivative topics to develop students' mathematical problem-solving abilities. The development model combines the Plomp and Gravemeijer & Cobb models, which are divided into the preliminary research stage, the development or prototyping stage, and the assessment stage. In the preliminary stage, needs analysis, curriculum analysis, concept analysis, and literature review are carried out. Product prototype development is carried out at the development stage, and formative evaluation consists of self-evaluation, expert validation, one-to-one, and small group phases. In this article, the study focuses on findings from one-to-one activities at the development stage. Through one-to-one activities, the resulting design was tested on three students with different abilities to find out whether this product could later be implemented in the classroom. After students learn to use the design, at the end of the activity, students are given a problem-solving ability test to determine the impact of the design on students' problem-solving abilities. The final product obtained is Local Instructional Theory (LIT) of derivative topics, valid, practical, and impact students' problem-solving abilities of RME-based teacher and student books